Hermite wavelet based numerical method for the solution of two parameters singularly perturbed non-linear Benjamina-Bona-Mohany equation - S.C. Shiralashetti (Scientific African, 2021)
In this paper, the Hermite wavelet based numerical method is developed for the solution of two parameters singularly perturbed non-linear Benjamina-Bona-Mohany partial differential equation.Present method is purely based on the time discretization of Hermite wavelets series approximations with collocation technique. In order to check the efficiency of the proposed method, it is applied on well known equations are called two parameters singularly perturbed non-linear Benjamina-Bona-Mohany partial differential equation with different cases. Hermite wavelet based numerical solutions are obtained by preparing matlab codes of the proposed method and in comparision with the exact and existing methods of solution, it is presented in the form of figures and tables at different time levels. Absolute error is also calculated at the different time levels and presented in figures and tables to exhibit the accuracy and applicability of the proposed method.